Avaliação das atividades antinociceptiva, anti-inflamatória e gastroprotetora de Spondia tuberosa arruda (Anacardiaceae) em modelos experimentais - Falcão, Renata de Alencar (2014)
Spondia tuberosa Arruda (Anacardiaceae), popularly known as umbu, is found in the northeastern Brazilian semiarid region and is endemic to the caatinga. Presents a source of vitamins (B1, B2, A, C and niacin), minerals (calcium, phosphorus and iron) and a high antioxidant power, which reduces damage caused by reactive species such as the appearance of premature aging and degenerative diseases. The aim of this study was to evaluate the toxicity, antinociceptive, anti-inflammatory and gastroprotective the ethanol extract of the leaves of S. tuberosa (EEtOH-St) at doses 125 mg/kg, 250 mg/kg and 500 mg/kg. The survey was conducted in pharmacological testing laboratories and the development and testing of medicines (LABDEM) both located at the State University of Paraíba (UEPB). 40 Swiss albino mice, albino Wistar rats and 156 larvae of Artemia salina L. Given this, the toxicological evaluation was performed to determine the 50% lethal concentration (LC 50 ), acute toxicity and behavioral assessment were used, also observed the activity antinociceptive using the method of formalin. Although the evaluation of anti-inflammatory activity induced by carrageenan was performed and evaluated the non-steroidal gastroprotective action in models of ulcers induced by ethanol and anti-inflammatory drugs (NSAIDs). Bioassay with Artemia salina Leach, leaves extract showed low toxicity. A single dose of 2000 mg / kg of EEtOH-St in mice, did not cause behavioral changes in the evaluated parameters. Also did not cause changes in weight or the macroscopic structure of organs. Unable to determine the lethal dose 50 (LD 50 ) as there were no deaths at the end of the 14 days of observation. It was observed that the antinociceptive activity in the dose 125 mg / kg did not affect the response of the first phase of nociception and the dose 250 mg / kg EEtOH-St in the second stage had a greater inhibition (100%) than the anti-self inflammatory used as standard. In the evaluation of anti-inflammatory activity among the doses tested the extract, only 500 mg/kg was able to inhibit cell migration. Gastroprotective activity with respect to the doses 125, 250 and 500 mg/kg against induction of ulcer models ethanol decreased significantly the ulcerative lesion index (ULI) in 13.69%, 38.69% and 69 , 64%, respectively, and were able to change the evaluated corresponding to gastric volume parameter. In the assessment of NSAID-induced gastric ulcers model, inhibition of lesions was 44.56% for the dose 125 mg/kg, 39.13% for the 250 mg/kg, and 45.65% at 500 mg/kg. As for the induction of ulcers ethanol and pretreated with indomethacin model, the salt-extract group compared to saline-saline could inhibit ILU at 43.05%, and indomethacin-extract group compared to saline-indomethacin inhibited 50.37% the amount of ULI. Given these results, it is important that other experimental models to be tested, so you can demonstrate participation in this plant, anti-inflammatory and antinociceptive mechanisms gastroprotective.